2023
DOI: 10.1002/cre2.715
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic retreatment decision‐making: The influence of the framing effect

Abstract: Objective The aim of this study was to explore the influence of a framing effect in retreatment decision‐making of a root‐filled tooth with asymptomatic apical periodontitis (AP). Method Two variants of a questionnaire were created in which the factual information about a root filled with AP was identical. The options in the first variant were framed in favor to wait and see (FW) and those in the other variant were framed in favor of retreatment (FR) Two hundred and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…This ndings are consistent with those of earlier researches [26,27]. In our study, there were large inter-and intra-observer discrepancies during the interpretation of PR images by the general practitioners; this may be attributed to the diversity in decision-making in many cases due to a lack of knowledge and the buildup of experience that is needed to accurately diagnose endodontic cases [28,29]. In contrast, our results documented a high degree of inter-and intra-observer agreement with the use of CBCT images; this may be explained by Patel et a [30] who demonstrated that examiner expertise had no effect on the interpretation of CBCT images.…”
Section: Discussionsupporting
confidence: 93%
“…This ndings are consistent with those of earlier researches [26,27]. In our study, there were large inter-and intra-observer discrepancies during the interpretation of PR images by the general practitioners; this may be attributed to the diversity in decision-making in many cases due to a lack of knowledge and the buildup of experience that is needed to accurately diagnose endodontic cases [28,29]. In contrast, our results documented a high degree of inter-and intra-observer agreement with the use of CBCT images; this may be explained by Patel et a [30] who demonstrated that examiner expertise had no effect on the interpretation of CBCT images.…”
Section: Discussionsupporting
confidence: 93%
“…how information about the situation is conveyed) can be a decisive factor in itself. Certain words or phrases, which implicitly contain values, even if intended to provide neutral information, can demonstrably have a large impact on decision‐makers' choices (Kvist et al., 2023; Tversky & Kahneman, 1981). Our results showed that the decision aid was able to exert a positive educational and psychological effect on our patients, despite them choosing the same treatment decision after watching the video.…”
Section: Discussionmentioning
confidence: 99%
“…According to the prevailing academic paradigm, a root filled tooth with apical periodontitis is defined as an "endodontic failure" and thus implies a clinical decision and action (41,42). The repeatedly demonstrated variation in clinical decisions and in particular the reluctance among practitioners to institute retreatment has bothered scholars in endodontology since the 1980's (43).…”
Section: Decision Making Of a Root Filled Tooth With Apical Periodont...mentioning
confidence: 99%